SUSTAINABLE DESIGN, CONNECTIVITY ORDER AND DETAILING ARCHITECTURE TO SITE COMFORT, CORRIDOR BRAGA - Nurtati Soewarno; Taufan Hidjaz; Eka Virdianti (Dimensi: Journal of Architecture and Built Environment, 2018)
Comfort in activities is very instrumental to liven up interaction within the city community. In fact, public spaces of a city are developed by the comfort obtained physically and psychically, Braga Corridor which built with the typology adapting the European and the tropical. This architecture is believed to provide fun experience for interaction, which eventually develop the physically comfort. Unfortunately that the city economy growth can threaten the existence of the Corridor. We believed the comfort fact to be the keyword to solve the problem. This study was aimed at analyzing connectivity and comfort. Mixed method research approach was employed. The data was gathered by a measuring tool, observation, and documentation. The analyzed using descriptive method. The results showed that the Braga Corridor segment 2 has provided visual psychic comfort and architecturally assisted thermal comfort in the morning and afternoon shadowing aspect, but for the comfort of the thermal beyond comfortable temperature zones.